Inner child, can we play? An ethnographic narrative enquiry of personal play histories - Kersh, Yael Sara (My University, 2017)
The research consists of a practical arts-based research component and a research report that surveys the practice. This document serves as the written element of the research and investigates the key theoretical standpoints, methodologies applied and creative outcomes. The research aimed to explore the dynamics of adults and play within Drama Therapy by investigating the relationship between six adult women and their personal play histories. It questioned what play meant to the individual and invited her to share her most memorable playful moments through various forms of expression in a number of individual interview-discussions. Through a practical arts-based research approach, an ethnographic narrative inquiry unfolded about women, play, childhood memory and present adulthood. The research took these shared narratives and presented them back to the six participants through various playful methods. With the use of methodologies such as inter-subjectivity, playful listening, narrative enquiry and Playback Theatre, the research offered a series of representational reflections of the shared stories. The creative outcomes were presented in a storybook representation which used imagery and poetic rhyme to document each narrative, a stop-motion film that used moving image and voice, and an presentation-installation that invited each woman to engage with her playful inner-self reflected back to her. The report is written with these playful elements which attempt to mirror the creative representational outcomes, inviting the reader to access his or her playful self. Thematically, three key factors presented themselves throughout the five-stage research process. These include the emotional experience associated with play, the notion of an inner-child or childhood and play within context. All three elements are discussed in the research report, with the use of the contextual factor symbolised by road signs to represent the intersectionality of play and its relationship to the individual. The research presents a number of key contributing factors to the discussion of adults and play in Drama Therapy. It attempts to explore alternative ways of delving into therapeutic process while respecting individual perspectives and personal narratives. It highlights the fundamental value of play within a drama therapeutic paradigm and how the notion of play and play memories contribute to the adult self. It also affirms the role of arts-based practice as a powerful tool for validation and witnessing of clients.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts (Drama Therapy) November 2017
Keywords: Drama--Therapeutic use; Arts--Therapeutic use; Narrative therapy